Fully inkjet printed ultrathin microsupercapacitors based on graphene electrodes and a nano-graphene oxide electrolyte. Issue 21 (20th May 2019) - Sollami Delekta, Szymon; Adolfsson, Karin H.; Benyahia Erdal, Nejla; Hakkarainen, Minna; Östling, Mikael; Li, Jiantong
Abstract : Ultrathin all-solid-state microsupercapacitors with graphene electrodes and a graphene oxide electrolyte are fabricated entirely by inkjet printing. Abstract : The advance of miniaturized and low-power electronics has a striking impact on the development of energy storage devices with constantly tougher constraints in terms of form factor and performance. Microsupercapacitors (MSCs) are considered a potential solution to this problem, thanks to their compact device structure. Great efforts have been made to maximize their performance with new materials like graphene and to minimize their production cost with scalable fabrication processes. In this regard, we developed a full inkjet printing process for the production of all-graphene microsupercapacitors with electrodes based on electrochemically exfoliated graphene and an ultrathin solid-state electrolyte based on nano-graphene oxide. The devices exploit the high ionic conductivity of nano-graphene oxide coupled with the high electrical conductivity of graphene films, yielding areal capacitances of up to 313 μF cm −2 at 5 mV s −1 and high power densities of up to ∼4 mW cm −3 with an overall device thickness of only ∼1 μm.